Construção de um instrumento de avaliação de atitudes frente à história da ciência e sua utilização no ensino - Scoaris, Raquel Carmen de Oliveira (2007)
Several researches have defended the inclusion of the History of Science in the training of the Science teacher by stating that the teacher must have a minimum knowledge of the social aspects of Science. Knowledge on the attitudes of students on this theme is of paramount importance. Attitudes may be analyzed by evaluations that would give clues on their opinions and, consequently, their influence on pedagogical practice may be inferred. A metric scale evaluation tool has been prepared in current research to assess the attitudes of undergraduate Science (Physics, Chemistry, Biology, Geography and Math) students with regard to the History of Science in teaching. Initially 96 items, based on a research in the literature on the History of Science and its employment in teaching, were presented. Each item corresponded to a statement that must be answered by a Likert-type scale. Items were grouped under five headings: I Knowledge of the History of Science (HS); II Acknowledgement that HS is important; III Acknowledgement that HS is relevant in teaching; IV Influence of HS in the teacher's training; V The teacher and his/her relationship with the HS. The above tool was initially evaluated by eleven judges, experts in the History of Science, Education and Psychology, who opined on the clarity and classification of each item and its appropriateness. Items were reduced to 89 and the tool was applied to a sample of 201 students of the 2nd, 3rd and 4th year of the undergraduate course mentioned above at a university in the state of Paraná, Brazil. Statistical analyses by SPSS® v.13 were applied to the answers as a validity test. Descriptive, trust and factorial analyses were further undertaken, while certain lowsignificant items or items that proved to be difficult to reply by sampled students were eliminated. Results showed factorial loads between 0.799 and 0.373 and alphas 0.921, 0.716 and 0.581 respectively, for a 33-item questionnaire, subdivided into three factors I. Importance of the History of Science in teaching; II Insecurity with regard to the History of Science; III Knowledge of History and the nature of Science. Results also show that the above tool has psychometric traits proper for the evaluation of undergraduate students' attitudes with regard to the History of Science in teaching.